Indications and outcomes of resident‐performed cataract surgery requiring return to the operating room. Issue 3 (March 2016) - Schmidt, Caroline M.; Sundararajan, Miel; Biggerstaff, Kristin S.; Orengo‐Nania, Silvia; Coffee, Robert E.; Khandelwal, Sumitra S.
Abstract : Purpose : To identify the clinical and operative factors predicting reoperation within 30 days of resident‐performed cataract surgery and correlate them with 1‐year visual outcomes. Setting : Michael E. DeBakey Veterans Affairs Medical Center, Houston, Texas, USA. Design : Retrospective cohort study. Methods : The study assessed patients who had resident‐performed cataract surgery between 2005 and 2013 and required return to the operating room for a second surgery on the same eye within 30 days. Preoperative and intraoperative risk factors were assessed. Outcome measures included corrected distance visual acuity (CDVA) at 1 year. Results : A review of 6644 resident‐performed cataract surgeries showed that 54 eyes (0.85%) of 54 patients required a return to the operating room within 30 days. The reoperation rate was higher in the first half of the academic year (1.18%) than in the second half (0.55%) ( P = .004). The mean CDVA 1 year postoperatively was 20/40, with a loss of lines of vision in 4 eyes. The mean operative time was 59.23 minutes ± 35.05 (SD). A longer intraoperative time was predictive of a worse visual outcome ( P < .01). Conclusions : Despite the need for reoperation within 30 days, most patients achieved improved visual acuity. The reoperation rate was significantly lower in the second half of the academic year. Increased operation times correlated with worse visual acuity independent of other variables. Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.